Analisis Citra Merk Melalui Strategi Branding Media Sosial Instagram Universitas Negeri Jakarta - Syifa Nabila; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze the branding strategies implemented by Universitas Negeri Jakarta (UNJ) through the Instagram social media platform to see their brand image. The study employed a field study with a descriptive qualitative research approach. Data collection techniques were conducted through interviews, observations, and documentation. The results of the research indicate that UNJ has successfully built a strong and positive image through a consistent approach in highlighting academic achievements, campus activities, and cultural diversity. Active interaction with users has also proven to be key in strengthening the relationship between UNJ and their Instagram audience. Additionally, clear differentiation in emphasizing unique advantages and the distinctive identity of UNJ significantly contributes to distinguishing UNJ's brand from other educational institutions. However, challenges such as maintaining consistent user engagement need to be addressed through improved research and more innovative content strategies in the future. Therefore, this research provides valuable insights for marketing and branding practitioners in developing more effective strategies on social media platforms..